Siebie samych się boicie! Polska w kinie niemieckim po 1989 roku - Puto, Kaja (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article is devoted to the image of Poland in German cinema after 1989. First, I present arguments against adopting the postcolonial approach, as it is insufficient for a complete critical description of this phenomenon, as well as inconsistent with the foreign policy of the united Germany. Next, I analyze the role of money as requisite, interpreting the film image of Poland as a caricature of Western rationality – a reality in which no other logic is possible apart from the logic of money (which is taboo in contemporary Germany).